Creating Jobs in India's Organised Manufacturing Sector - Radhicka Kapoor (Indian Council for Research on International Economic Relations (ICRIER), 2014)
Despite witnessing a decade of rapid economic growth, an acceleration of growth in the organised manufacturing sector has eluded India. Using data from the An nual Survey of Industries, we examine the factors holding back the growth of output and employment in this sector. We find that there are heterogeneities in the performance of the manufacturing sector across industries and states. Recent economic growth has benefited industries which rely more on capital and skilled workers as opposed to unskilled/low skilled workers. This fact combined with the rising capital intensity of production over the decade partly explains the limited contribution of the manufacturing sector to employment generation. At the state level, we find that states with more inflexible labour regulations have witnessed slower growth in employment and output in manufacturing than states with more flexible labour market regulations. However, it would be incorrect to put the entire onus of the dismal performance of the manufacturing sector on labour regulations as firms are responding to rigidities in the labour market in innovative ways such as the greater use of contract workers. Factors such as cumbersome product market regulations and infrastructural bottlenecks have also adversely affected the growth of the manufacturing sector. Given that the days of industrial licensing are gone and markets are influenced not only by regulations enacted by central government, but also those enacted by state governments, much of the action for improving the business environment needs to be taken at the state level.
Keywords: E24; D24; J40; J50; L60; 330; Organised Manufacturing; Output Growth; Employment Growth; Labour Intensity; Labour Regulations; Contract Workers